Access to Public Administration Information in Mexico: regulation of the Free Information Principle - GARCÍA LÓPEZ, GENARO LUIS (Investigación Bibliotecológica. Archivonomía, bibliotecología e información, 2007)
THE LAW OF ACCESS TO PUBLIC INFORMATION IN THE STATE OF SINALOA, AND THE FEDERAL LAW OF TRANSPARENCY AND ACCESS TO PUBLIC GOVERNMENTAL INFORMATION ARE ANALYSED WITHIN THE FRAMEWORK OF THE KNOWLEDGE SOCIETY, THE DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGIES, THE FIGHT AGAINST CORRUPTION AND THE DEVELOPMENT OF E-GOVERNMENT AND E- ADMINISTRATION IN MEXICO. GENERAL PRINCIPLES OF LAW SUCH AS THE RIGHT OF ACCESS TO PUBLIC INFORMATION, PRIVACY OF PERSONAL DATA AND PROTECTION OF PRIVATE AND CONFIDENTIAL DATA ARE ANALYSED; "PUBLIC INFORMATION" AND "PUBLIC DOCUMENT" ARE DEFINED; CRITERIA FOR THE CLASSIFICATION OF INFORMATION ARE ESTABLISHED; THE GOVERNMENT BODIES AFFECTED ARE SPECIFIED, AND ALSO THE CRITERIA FOR ESTABLISHING THE COST OF ACCESS AND DIFFERENT PROCEDURES FOR THE DEVELOPMENT OF THE LAWS. A SUBSEQUENT STUDY IS MADE OF THE DEVELOPMENT OF THE REGULATIONS AND THE CREATION OF INSTITUTIONS OR AGENCIES TO FULFIL THE LEGISLATIVE PRECEPTS. THE PAPER CONCLUDES BY POINTING OUT THE LIMITATIONS IN THE DEVELOPMENT OF FREE ACCESS TO INFORMATION AND THE LACK OF INTEREST OF MOST CITIZENS, AND THE CHALLENGES POSED BY THE NEW FRAMEWORK FOR INFORMATION SCIENTISTS, DISCUSSED.